2019
DOI: 10.1007/s00438-019-01616-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci for starch-corrected chip color after harvest, cold storage and after reconditioning mapped in diploid potato

Abstract: The objective of this study was to map the quantitative trait loci (QTLs) for chip color after harvest (AH), cold storage (CS) and after reconditioning (RC) in diploid potato and compare them with QTLs for starch-corrected chip color. Chip color traits AH, CS, and RC significantly correlated with tuber starch content (TSC). To limit the effect of starch content, the chip color was corrected for TSC. The QTLs for chip color (AH, CS, and RC) and the starch-corrected chip color determined with the starch content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Most agronomic traits of potato are of quantitative nature. This means they are governed by multiple genetic factors including regulatory genes, microRNA, preferential and multiple alleles (e.g., starch and chip color, potato tuber greening, tuber shape, specific gravity) (Schäfer-Pregl et al 1998 ; Śliwka et al 2016 ; Sołtys-Kalina et al 2020b , a ; Plich et al 2020 ; Park et al 2021 ). The quantitative nature of interactions at the genome level creates the risk that genetic manipulation of one gene/allele will not change the phenotype and that the desired trait will not be achieved.…”
Section: Potato As a Target Plant For Crispr/cas Genome Editing Techn...mentioning
confidence: 99%
“…Most agronomic traits of potato are of quantitative nature. This means they are governed by multiple genetic factors including regulatory genes, microRNA, preferential and multiple alleles (e.g., starch and chip color, potato tuber greening, tuber shape, specific gravity) (Schäfer-Pregl et al 1998 ; Śliwka et al 2016 ; Sołtys-Kalina et al 2020b , a ; Plich et al 2020 ; Park et al 2021 ). The quantitative nature of interactions at the genome level creates the risk that genetic manipulation of one gene/allele will not change the phenotype and that the desired trait will not be achieved.…”
Section: Potato As a Target Plant For Crispr/cas Genome Editing Techn...mentioning
confidence: 99%
“…The population 11-36 (N = 149), originated from cross between diploid potato clones DG 06-5 and DG 03-226, was sown in 2011 and was used to map QTL for tuber morphology traits, as well as for tuber blackspot bruise and enzymatic discoloration susceptibilities [22,23]. The population 12-3 (N = 183) obtained from a cross between DG 00-683 and DG 08-28/13 and sown in 2012, served for mapping QTL for tuber starch content and chip color [24][25][26]. The parental forms of both populations resulted from a recombinant breeding program at IHAR-PIB that included in their pedigree a number of Solanum species: S. tuberosum, S. acaule, S. chacoense, S. demissum, S. gourlayi, S. microdontum, S. phureja, S. stenotomum, S. verrucosum, and S. yungasense.…”
Section: Plant Materialsmentioning
confidence: 99%
“…The most challenging aspect of the research is the characterization of causal variants, the validation of gene functions, and the identification of protein networks. Recent research has demonstrated a correlation between the expression level of allele variants, traits, and expression variance, increasing the confidence in candidate gene detection [17]. A combination of accurate phenotyping, advanced genetic materials, and genomic techniques is considered as an alternative approach to improve the ability to detect genes associated with characteristics.…”
Section: Introductionmentioning
confidence: 99%